Composition, Distribution, and Fisheries Biology of Penaeid Shrimp from the Strong Wavy Waters of Southern Java, Indonesia - Rianti Pratiwi; Wanwan Kurniawan; Ayuningtyas Indrawati; Putri Sapira Ibrahim; Muhammad Hafizt (Universitas Diponegoro, 2023)
Penaeidae is a family of shrimp that has a high economic value, leading to intensive exploitation in many areas. This research was conducted to ascertain the composition, distribution, and fisheries biology of Penaeid shrimps in the strong wavy water of southern Java Island, Indonesia. The research locations were the water of Eastern, Central, and Western Java. Shrimp samples were obtained using various ways. The carapace length (CL) of the shrimps were measured using plastic callipers and recorded to the nearest 1 mm. The results showed that eight species of shrimps were caught in the water of southern Java, with Penaeus merguiensis, P. semisulcatus, and P. monodon being the most common. The species P. merguiensis was found in each sampling location, while P. latisulcatus and Metapenaeus palmensis were only present at Drini Beach (Central Java). The results also showed that P. japonicus and M. lysianassa were only found at Ranca Buaya Beach (West Java). The species P. merguiensis and P. monodon were the two most commercially important species. The distributions of the shrimps were related to the water physical characteristics associated with the shrimp habitat namely SST, bathymetry, and tides. Fishery biology analysis found that the length at first impregnation of P. merguiensis at Damas and Sidem Water (East Java) was 25.9 cm CL. Furthermore, the LBSPR analyses revealed that the spawning capacity of P. merguiensis and M. ensis in the same waters were still very high under the current level of exploitation. Therefore, the magnitude of fishing has not endangered the sustainability of the two shrimps.